NIEWYKONANIE ZOBOWIĄZANIA Z UMOWY PRZEDWSTĘPNEJ W OBROCIE NIERUCHOMOŚCIAMI. ODPOWIEDZIALNOŚĆ ODSZKODOWAWCZA - Mróz, Arkadiusz (Zeszyty Prawnicze, 2016)
Non-Performance in a Preliminary Agreement in Property Transfer. Liability for Damages Summary This is the second of three articles presenting a detailed discussion of the legal construction of the preliminary agreement, as well as its significance and potential application in property transfer. It presents aspects of the performance of the obligation defined in the preliminary agreement and the consequences of non-performance, the division of preliminary property sales agreements into agreements with stronger or weaker effects, the scope and the amount of damages due to the event of non-performance of the preliminary agreement by the obliged party, and the consequences of stipulating a penalty in the preliminary agreement and making a down payment upon its conclusion.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />